Composite Fibers: Hydrophobic Microfiber Strain Sensor Operating Stably in Sweat and Water Environment (Adv. Mater. Interfaces 24/2018). Issue 24 (20th December 2018) - Jeong, Sang‐Mi; Kang, Youngsoo; Lim, Taekyung; Ju, Sanghyun
Abstract : A (1H, 1H, 2H, 2H‐heptadecafluorodec‐1‐yl) phosphonic acid‐coated polyurethane–tin oxide–carbon nanotube composite microfiber as a strain sensor, with large stretchability and high stability, can accurately monitor human joint motion suggesting that it can be applicable to detect all minute bending movements in the elbow and knee with a multidimensional angular fabric configuration and predict disease with a healthcare monitoring system. More details can be found in the article number1801376 by Sang‐Mi Jeong, Sanghyun Ju, and co‐workers.